Sobrietology in Social Advertising - M. A. Nikolaeva; V. D. Shirshov; S. V. Shirshov (Russian State Vocational Pedagogical University, 2015)
The paper discusses the role of social advertising in promoting the ideas of a sobrietology - the science exploring the negative phenomena affecting human consciousness, investigating the conformities of human society, where the sobriety is a vitally important norm and value, and taking psychoactive substances is limited to the non-affecting the individual and society minimum. Sobrietology emphasizes psychic processes, interpersonal pedagogical interactions and social prospects of a healthy nation. This field of human knowledge can guarantee the necessary assistance to teachers in counteracting the tobacco smoking, taking alcohol, narcotics and toxic substances. The authors denote the structural aspects of sobrientology, its pedagogical guidelines and demonstrate the possible ways of social advertising in educational sphere, developing the ideals of moral and physical health, and steady socially adequate behavior patterns. Social advertising is regarded as the relevant new resource in propagating the healthy and sober life style, and providing the grounds for personal growth. It combines the informational, communicative, educational, patriotic and image-making functions and possesses a powerful potential of influencing people's consciousness and behavior. In the authors' opinion, this sort of informational activity is quite perspective and efficient for promoting the ideas of sobriety, sustaining the moral norms and values, and carrying the state anti-alcohol and anti-narcotic policy.